Decoding the aroma of Rosa canina L.: Chemical composition and gene expression. - Parisa Jariani; Ali-Akbar Shahnejat-Bushehri; Roohangiz Naderi; Meisam Zargar; Mohammad Reza Naghavi (PLoS ONE)
Objective The aromatic profile of Rosa canina L. petals hold immense potential for the fragrance and pharmaceutical industries. This study aims to investigate the chemical composition and gene expression patterns across different floral development stages to uncover the biosynthetic pathways of floral scent. Methods Essential oils (EOs) were extracted from petals at five developmental stages (S1-S5) and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS), identifying 20 distinct compounds. RNA isolation and quantitative real-time PCR (qRT-PCR) analysis were performed to assess gene expression. Results Stage S3, notable for its enhanced aromatic profile, was dominated by terpenoid compounds such as β-Citronellol (1.18%), Caryophyllene (8.59%), β-Selinene (1.50%), and Caryophyllene oxide (0.50%), indicating significant upregulation of terpenoid biosynthesis genes. qRT-PCR analysis revealed that CCD1 had the highest expression in S4 (9.51-fold), while DXR and DXS peaked at S3 with fold changes of 29058.38 and 73.35, respectively. Other genes like AAT1, LIS, and GPS also showed peak expressions at S3 with fold changes of 1.33, 10.70, and 1.18, respectively. PAR exhibited the highest expression in S1, while GGPPS peaked in S4 (2.01-fold). Clustering analysis indicated distinct groupings of developmental stages and gene expression patterns, with strong correlations between specific genes and compounds, such as CCD1 with GGPPS (0.78) and β-Citronellol with Caryophyllene (0.92). Principal Component Analysis (PCA) highlighted significant contributions of AAT1, GPS, and nonadecane compounds to the overall variance. Conclusion These findings provide a comprehensive understanding of the chemical and genetic factors shaping the aromatic profile of R. canina, with promising applications for both the fragrance and pharmaceutical sectors. The study's innovation lies in the detailed correlation between EO composition and gene expression, presenting new insights into the biosynthetic pathways of floral scent.